2021
DOI: 10.1111/ibi.12967
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of the White‐tailed Sea Eagle (Haliaeetus albicilla): post‐fledging behaviour, natal dispersal onset and the role of the natal environment

Abstract: Exploratory movements and natal dispersal form essential processes during early life history stages of raptors, but identifying the factors shaping individual movement decisions is challenging. Global positioning system (GPS) telemetry thereby provides a promising technique to study movement patterns on adequate spatio‐temporal scales. We analysed data of juvenile White‐tailed Sea Eagles Haliaeetus albicilla (WTSE) in north‐east Germany (n = 24) derived from GPS tracking to extensively analyse movements betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
(177 reference statements)
3
10
0
Order By: Relevance
“…In the study area, white‐tailed eagles start courtship in January–February, nest in March, and lay eggs from late March to late April (the authors' observation). The incubation period is 37–38 days (Müller, 2010), and a brood is fed in the nest for 70–90 days (Engler & Krone, 2022; Mori, 1980; Müller, 2010). The fledging varies from early July to August (the authors' observation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study area, white‐tailed eagles start courtship in January–February, nest in March, and lay eggs from late March to late April (the authors' observation). The incubation period is 37–38 days (Müller, 2010), and a brood is fed in the nest for 70–90 days (Engler & Krone, 2022; Mori, 1980; Müller, 2010). The fledging varies from early July to August (the authors' observation).…”
Section: Methodsmentioning
confidence: 99%
“…Juveniles are vagrant and search for a breeding site long before maturation. Juveniles leave their parental territory 92 days after fledging and make various excursions from their natal site (Engler & Krone, 2022). Nemesházi et al (2018) reported territory intrusions in seven of 11 territories, and those intrusions were done mainly by juveniles, which were not offspring of resident pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2017, DOF BirdLife and the Natural History Museum of Denmark have monitored Danish WTEs with the use of GPS tracking technology to acquire detailed knowledge of their movements. Other studies of the species using GPS technology have been carried out in other European countries, including Croatia [15], Czech Republic, Hungary, Austria [16], Finland [17], Germany [18][19][20], Ireland [3], and Norway [21].…”
Section: Introductionmentioning
confidence: 99%
“…We still lack detailed knowledge of natal dispersal movements in Denmark, even though it is a vital process affecting both the dynamics, size, and gene flow of a population [23]. Dispersal is a complex subject, and many factors seem to affect dispersal in raptors, both internal and external such as resource availability, quality of the natal habitat, and sex, and this has been the focus of several studies in recent years [4,16,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…The study of juvenile dispersal has attracted the interest of ecologists and evolutionary biologists dedicated to biodiversity conservation [ 4 ]. However, the study of dispersal movement may be difficult in those species in which the movement capacity is high, and some individuals may leave the boundaries of the study area [ 5 , 6 , 7 , 8 ]. On many occasions, it is hard to know if marked individuals remain undetected because they have moved outside the investigators’ detection area or because they have not survived [ 9 ].…”
Section: Introductionmentioning
confidence: 99%